A quantitative study on the cement companies of DSE listed firms of Bangladesh for the period of 2010 to 2015 - Dhrubo, Rashidul Haque (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.